High-risk human papillomavirus in HIV-infected women undergoing cervical cancer screening in Lilongwe, Malawi: a pilot study. (May 2015) - Reddy, Deepa; Njala, Joseph; Stocker, Penny; Schooley, Alan; Flores, Martiniano; Tseng, Chi-Hong; Pfaff, Colin; Jansen, Perry; Mitsuyasu, Ronald T; Hoffman, Risa M
Rates of abnormal visual inspection with acetic acid and prevalence of high-risk human papillomavirus (HPV) subtypes have not been well characterized in HIV-infected women in Malawi. We performed a prospective cohort study of visual inspection with acetic acid (N = 440) in HIV-infected women aged 25--59 years, with a nested study of HPV subtypes in first 300 women enrolled. Of 440 women screened, 9.5% (N = 42) had abnormal visual inspection with acetic acid with 69.0% (N = 29) having advanced disease not amenable to cryotherapy. Of 294 women with HPV results, 39% (N = 114) of women were positive for high-risk HPV infection. Only lower CD4 count (287 cells/mm 3 versus 339 cells/mm 3, p = 0.03) and high-risk HPV (66.7% versus 35.6%, p < 0.01) were associated with abnormal visual inspection with acetic acid. The most common high-risk HPV subtypes in women with abnormal visual inspection with acetic acid were 35 (33.3%), 16 (26.7%), and 58 (23.3%). Low CD4 cell count was associated with abnormal visual inspection with acetic acid and raises the importance of early antiretroviral therapy and expanded availability of visual inspection with acetic acid. HPV vaccines targeting additional non-16/18 high-risk HPV subtypes may have greater protective advantages in countries such as Malawi.